Control of hexagonal boron nitride dielectric thickness by single layer etching. Issue 21 (12th April 2019) - Ma, Zichao; Prawoto, Clarissa; Ahmed, Zubair; Xiao, Ying; Zhang, Lining; Zhou, Changjian; Chan, Mansun
Abstract : Single layer etching of h-BN is achieved using a two-step remote plasma process. Abstract : This work demonstrates a layer-by-layer etching technique to control the hexagonal boron nitride (h-BN) film thickness with single layer precision. The method involves top layer h-BN deformation via oxygen-radical adsorption and then top layer removal by nitrogen-ion bombardment. An ultimate monolayer h-BN with a smooth surface can be obtained from a thick flake by using the method repeatedly. The mechanism of the single layer h-BN etching is verified using X-ray photoelectron spectroscopy analysis and first principle molecular dynamics. Characterization of the dielectric properties of a thickness-reduced h-BN film shows a desirable low leakage current, large capacitance and high breakdown field properties as a gate dielectric material.